Waste to resource under grinding-flotation combination: The collision of hazardous carbon dross and waste engine oil - Ningning Feng; Lijia Peng; Bin Li; Jieqiang Zhou; Xi Liu; Zhaohui Cheng; Qiang Huo (Minerals Engineering, 2026)

Shape-finding for a triple-tower spatial double-cable suspension bridge with upper hangers - Wei Liu; Li Zhu; Xue-Jin Huo; Xiao-Wei Ma; Jia-Huan Li; Xu-Xu Cheng (Engineering Structures, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Microscopic leaching mechanism of cryolite impurities in coarse carbon products after carbon dross flotation: DFT, MD, and experiments - Yunkang Sun; Wenjie Yu; Shijie Chen; Zhaohui Cheng; Qi Wang; Chunqiang Chen; Jieqiang Zhou; Xupang Liu; Xi Liu; Qiang Huo (Journal of Environmental Chemical Engineering, 2026)

A review on modified biochar-activated persulfate systems for degradation of aqueous organic pollutants: Mechanisms, applications, and future perspectives - Yushu Wang; Bin Li; Mingqian Cheng; Yue Zhao; Qingqing Huo; Xiangxi Zhang; Beibei Xu; Hengliang Zhang; Zewei Liu (Desalination, 2026)

Dynamic soft-templating of highly polymerized carbon nitride enabling potentiated visible light-driven NH2Cl activation: A synergistic self-amplifying ROS/RNS cascade toward water remediation - Xingbo Yin; Qixun Zou; Yaqi Yong; Xiaowei Huo; Xin Cheng; Yuling Tang; Jiguang Du; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Microbial and enzymatic synergy in process-intensified ensiling: A biorefinery strategy for corn stover valorization toward lactic acid and bioethanol - Jinge Deng; Shumin Cheng; Guofang Chen; Jiajin Sun; Xueyan Bao; Guangwen Zhang; Gang Guo; Wenjie Huo; Lei Chen (Biomass and Bioenergy, 2026)

Heterologous expression of Arabidopsis RLP30 enhances fungal resistance in poplar - Lijuan Zhao; Qiang Cheng; Xiaodie Huo; Conghui Li; Bingqing Li; Xueqin Meng; Qi Li; Rui Sun; ZeYao Li; Haitao Liu (Physiological and Molecular Plant Pathology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

High-permeability nanophotosensitizer eliminates biofilm-associated infection through concurrent lipid peroxidation and extracellular DNA degradation - Xiaochun Xie; Ziming Huo; Shaowen Wang; Jiying Liu; Chenyang Guo; Huantai Luo; Chuanxu Cheng; Wen Sun; Shan Guan; Panpan Chang; Dan Shao; Ronghua Yang (Chemical Engineering Journal, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Pharmacological interventions targeting cognition and related clinical outcomes in vascular dementia: a systematic review and meta-analysis of randomized controlled trials - Tianyu Cheng; Lin Zhang; Yizhou Zhang; Huazheng Liang; Junyan Wang; Gengzhen Chen; Yujia Huo (European Journal of Clinical Pharmacology, 2026)
Purpose Randomized evidence for pharmacological interventions in vascular dementia (VaD) is fragmented. We conducted a VaD-focused, scale-specific systematic review and meta-analysis. Methods We searched four databases for English-language parallel-group randomized controlled trials (1990–2025). Comparable placebo-controlled outcomes were pooled using random-effects meta-analysis; non-poolable outcomes were synthesized according to SWiM. Risk of bias and certainty were assessed with RoB 2 and GRADE. Results Sixteen trials included 5,668 participants across trial cohorts; with one exception, all were published in 2012 or earlier. EGb 761 ® was evaluated in three trials; nimodipine, galantamine, memantine, and rivastigmine in two each; and pentoxifylline, citicoline, sulodexide, donepezil, and Tianzhi granule in one each. Galantamine reduced ADAS-Cog/11 scores (2 trials, n = 1,332; MD − 2.01, 95% CI − 3.18 to − 0.85) and ADAS-Cog/13 scores (2 trials, n = 1,328; MD − 2.51, 95% CI − 3.87 to − 1.15), and memantine reduced ADAS-Cog/11 scores (2 trials, n = 752; MD − 2.20, 95% CI − 3.24 to − 1.15); certainty was moderate. EGb 761 ® reduced SKT scores (3 trials, n = 283; MD − 2.65, 95% CI − 5.17 to − 0.12), but heterogeneity was extreme (I²=92.8%; very low certainty). Galantamine showed no clear NPI benefit (2 trials, n = 1,310; MD − 0.13, 95% CI − 4.05 to 3.79), and memantine showed no clear GBS benefit (2 trials, n = 595; MD − 1.93, 95% CI − 4.69 to 0.84). Evidence for the other seven interventions was mainly single-trial and non-poolable; functional and global outcomes did not establish consistent benefit. Conclusion Galantamine and memantine showed small short-term cognitive effects; EGb 761 ® suggested a fragile, very low-certainty signal; patient-important benefits remain uncertain.

Polar nanoscale pincers in a robust microporous MOF for selective C2H2 capture from CH4 oxidation mixtures - Meng-Yu Huo; Shui-Sheng Chen; Yu-Hao Qin; Jie Liu; Bing-Jie Ruan; Yue Zhao; Cheng-Bin Ma; Zi-You Zhang (Chemical Engineering Journal, 2026)

China’s air pollution: Remarkable progress and ongoing challenges under new standards from combined surface-satellite observations (2015–2024) - Yujia Chen; Zhuang Wang; Congzi Xia; Xintong Chen; Yanfeng Huo; Shangpei Xun; Wenyu Wu; Binfang He; Hongqun Zhang; Jiaqi Chen; Xingxing Jiang; Cheng Liu; et al. (Journal of Hazardous Materials, 2026)

Dual-tuning of morphology and coordination in single-atom catalysts via organic linker engineering for singlet oxygen-dominated Fenton-like reactions - Hongda Liu; Weiping Xiong; Yang Liu; Guangfu Wang; Ziwei Wang; Chengyun Zhou; Biao Song; Xiuqin Huo; Guangming Zeng; Min Cheng (Journal of Hazardous Materials, 2026)

Multiple benefits of biochar for remediating contaminated mining soils: heavy metal stabilization, carbon sequestration, and ecological function restoration - Yibo Cheng; Weiying Feng; Yu Wang; Fang Yang; Qingfeng Miao; Chiamin Ho; Yaoqiang Huo; Haiqing Liao (Chemical Engineering Journal, 2026)

Fipronil and its transformation products in the Pearl River Estuary: Spatial distribution, bioaccumulation, trophic transfer and risk assessment - Lisha Ma; Can Huo; Yuhan Xie; Yi Yin; Qi Shan; Cheng Zhao; Shugui Liu (Marine Pollution Bulletin, 2026)

Removal of Microcystis aeruginosa by Fe-doped biochar via persulfate activation: Catalytic performance and mechanistic exploration - Tiantian Li; Zhiwen Cheng; Lili Yan; Guofeng Shang; Zongdi Hao; Guoqing Shen; Pinhua Rao; Runkai Wang; Guanghui Li; Zhaoziyue Zhang; Benjiao Huo (Journal of Environmental Chemical Engineering, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Exploratory observation of dietary exogenous bile acids on growth, hepatic glucose metabolism, intestinal and liver health, and fillet quality of Monopterus albus fed high-carbohydrate diets - Jiamin Li; Peng Fang; Ao Luo; Luyao Xu; Tianlun Luo; Junzhang Han; Tingting Li; Xiaoxuan Qi; Shuo Cheng; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2026)

Rapid crustal uplift during the Late Triassic in the Sulu orogenic belt, eastern China: Single-grain biotite Rb Sr isochron dating the Jiazishan syenite pluton - Dongyang Huo; Weiyong Li; Naizhen Zhang; Jingxin Zhao; Hong Cheng; Jun He; Fukun Chen (Lithos, 2026)

Corrigendum to “Responses of sugar metabolism to nitrogen fertilization in Lonicera caerulea: insights from integrated targeted metabolomics, transcriptomics, and molecular docking” [Food Chem. 502 (2026) 147759] - Liangchuan Guo; Jinli Qiao; Qinghai Sheng; Lingling Cheng; Xin Jin; Junqi Wang; Junwei Huo; Dong Qin (Food Chemistry, 2026)

Fe-Ni-MOF-derived NiFe2O4/NiO heterostructure for detection of 2-CEES at ppb level - Duo Zhang; Ying-Nan Dou; Rui Gao; Xian-Fa Zhang; Hui Zhao; Xiao-Li Cheng; Shan Gao; Ying-Ming Xu; Li-Hua Huo (Chemical Engineering Journal, 2026)

Metagenomic mining and functional reconstitution of hexanoic acid biosynthetic enzymes from Baijiu pit bottom - Xinjian Wang; Xuehui Huo; Huannuo Hu; Yumei Wang; Wenwen Cheng; Yupeng Wang; Chunhong Sun; Xiaole Wu; Yefu Chen (Bioresource Technology, 2026)

Comprehensive evaluation system for amendment selection: A case study of degraded black soil improvement - Yue Xie; Donghao Ma; Yongqi Zhang; Yuxin Cheng; Qingyun Wang; Yawen Huo; Samama Tariq; Jiabao Zhang (Journal of Environmental Management, 2026)

A copper-enhanced magnetic biochar-laccase composite achieves synergistic removal of tetracyclines - Xiangyue Xu; Meixia Huo; Qiuqi Cheng; Lei Sun; Mengya Fang; Xiaoqian Li; Hanyu Wang; Guyue Cheng; Lingli Huang (Chemical Engineering Journal, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Synthesis and Characterization of Terpyridine Derivatives as Fluorescence Probe for Selective Detection of Ga3+ Ions in Acidic Conditions - Erfu Huo; Mikhail Atroshko; Ming Feng; Pengfei Yang; Weiqin Cheng; Congcong Zhao; Siyamak Shahab; Yanhua Wang; Nasrin Masnabadi (Journal of Fluorescence, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Green deep eutectic solvents functionalized magnetic UiO-66-NH2: A novel strategy for improved stability and adsorption of BPA - Runan Chen; Zhao Li; Guohao Cheng; Mengyuan Zhang; Geer Huo; Yongli Liu; Guifen Zhu (Journal of Environmental Management, 2026)

Study on the mechanism of Na and Ca synergistically promoting the production of hydrogen-rich syngas by Zhundong coal gasification - Derui Chen; Mingming Pei; Ruiqiang Huo; Huiyun Cheng; Nan Xue; Hui Zhu; Luxiang Wang; Jiao Yin (Fuel, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

SnO2 sensor driven by crystal surface engineering: Innovative force for NO2 monitoring in smart agriculture - Weiqi Meng; Ming Zheng; Taifeng Zhang; Xianfa Zhang; Yuying Xin; Chuanyu Guo; Xiaoli Cheng; Xin Dong; Lihua Huo; Zongshuang Cao; Yingming Xu (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

POINT: a web-based platform for pharmacological investigation enhanced by multi-omics networks and knowledge graphs - Zihao He; Liu Liu; Dongchen Han; Kai Gao; Lei Dong; Xiaoning Qi; Dechao Bu; Peipei Huo; Zhihao Wang; Xuan Fan; Jingming Sun; Shuangshuang Lei; et al. (Science Bulletin, 2026)

Responses of sugar metabolism to nitrogen fertilization in Lonicera caerulea: insights from integrated targeted metabolomics, transcriptomics, and molecular docking - Liangchuan Guo; Jinli Qiao; Qinghai Sheng; Lingling Cheng; Xin Jin; Junqi Wang; Junwei Huo; Dong Qin (Food Chemistry, 2026)

Machine learning prediction of post-earthquake debris flows incorporating hydrological variables - Xiao-jian Wang; Zhen-lei Wei; Tian-xiang Liu; Chen-wen Guo; Cheng-yong Fang; Jing-kan Huo (Natural Hazards, 2026)

Design, synthesis and antitumor activity of thiadiazole derivatives as novel ALK kinase inhibitors - Yiwen Huo; Qinjiang Zhou; Cheng Zhang; Yanna Lv; Rongfei Liu; Mingyue Hou; Xiaoxuan Duan; Yue Liu; Jinxing Hu (Molecular Diversity, 2026)

An improved spatial-dependent model of neutron multiplicity counting for large-volume plutonium solution - Jia-Cheng Wang; Xiao-Dong Huo; Hai-Feng Yang; Zeng Shao; Kan Wang (Annals of Nuclear Energy, 2026)

Overexpression of peroxiredoxin 6 in bone marrow-derived mesenchymal stem cells amplifies their in vivo effect on bronchopulmonary dysplasia by increasing mesencephalic astrocyte-derived neurotrophic factor secretion - Huanqing Song; Qingfei Hao; Jingjing Li; Yuanyuan Liu; Zhifang Huo; Ranran Si; Xiaoxia Feng; Chuan Zhou; Xiuyong Cheng (Toxicology and Applied Pharmacology, 2026)

Diagenesis and burial history controls on Oligocene Huagang sandstones, southern Xihu Sag (East China Sea Basin): Implications for the formation of effective reservoirs - Hong-Liang Huo; Cheng-Lin Liu; Dao-Wu Huang; An-Qi Tian; Rizwan Sarwar Awan; Hong-Yan Gao; Chuang-Xin Liu; Xue-Yong Chen; Zi-Ye Tian; Tao-Zheng Yang; Bin-Bin Liu; Chao-Jun Liang (Marine and Petroleum Geology, 2025)

Pre-oxidized low-rank coal-based porous carbon aerogels for high-energy-density supercapacitors - Guangchao Hu; Junkai Chong; Fangqin Cheng; Xiangtao Huo; Min Guo; Mei Zhang (Chemical Engineering Journal, 2025)

Synergistic regulation of BFe2O4/Fe2O3 (B = Mn, Co, Ni, Cu) nanoarray materials by crystal plane and interface engineering for highly selective detection of 2-CEES gas - Baosheng Li; Ming Zheng; Qiuyue Zheng; Jiahui Li; Xin Dong; Xianfa Zhang; Lihua Huo; Xin Zhou; Xiaoli Cheng; Yingming Xu (Chemical Engineering Journal, 2025)

A multifunctional P/Si-containing imidazole curing agent toward advanced one-component epoxy resins with superior flame retardancy and mechanical properties - Cheng Wang; Haonan Wang; Guofeng Ye; Yong Guo; Qingshan Yang; Asim Mushtaq; Min Hong; Tielin Wang; Siqi Huo (Chemical Engineering Journal, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Enhanced catalytic degradation of sulfamethazine by magnetic N-doped biochar: Performance evaluation and mechanism insight - Mengcan Ju; Lili Yan; Zhiwen Cheng; Tiantian Li; Guanghui Li; Pinhua Rao; Qincheng Chen; Benjiao Huo (Process Safety and Environmental Protection, 2025)

Bio-based, selenium/Schiff base-containing co-curing agent enables flame-retardant, smoke-suppressive and mechanically-strong epoxy resins - Qian Zhong; Cheng Wang; Guofeng Ye; Zhenghong Guo; Ting Sai; Min Hong; Pingan Song; Hao Wang; Siqi Huo; Zhitian Liu (Chemical Engineering Journal, 2025)

Numerical simulation study on the influence of shearer mining intensity on dust distribution characteristics - Shihao Huo; Cheng Liu; Wei Ma; Fang Chen; Zhu Wang (Process Safety and Environmental Protection, 2025)

The mobility, host, and co-occurrence of antibiotic resistance genes in multi-type pig manure-soil systems: Metagenome assembly analysis - Xiangyue Xu; Xvdong Lin; Mengya Fang; Meixia Huo; Ziyan Kou; Wenjin Ma; Xiaoqian Li; Qiuqi Cheng; Hanyu Wang; Lingli Huang (Journal of Environmental Management, 2025)

Regulating the physicochemical and structural characteristics of extruded rice starch via complexation with ferulic acid - Jinjie Huo; Jiangkai Zeng; Yumin Duan; Peng Wang; Lishuang Wang; Zhuang Yang; Shiwen Cheng; Xiaoshuai Yu; Zhigang Xiao (Food Structure, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Design, synthesis and antitumour activity of pyrimidine derivatives as novel selective EGFR kinase inhibitors - Cheng Zhang; Yiwen Huo; Jianfang Fu; Yue Liu; Qinjiang Zhou; Mingyue Hou; Xiaoxuan Duan; Yanna Lv; Jinxing Hu (Molecular Diversity, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Interfacial electric field steering S-scheme charge transfer in MIL-88A(Fe)/polydopamine Heterojunctions: Dual-redox pathways for efficient pollutant mineralization - Bo Shen; Hao Du; Aoxiang Liu; Ningyi Li; Cheng Chen; Liguo Shen; Yuxin Hui; Rubin Huo; Zhe Zhang; Qi Wang (Journal of Cleaner Production, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Postharvest fruit rot on blue honeysuckle (Lonicera caerulea L.) caused by Penicillium oxalicum newly reported in China - Haohao Yan; Yuxuan Li; Yusheng Lv; Xin Zhao; Zijian Man; Zexu Chen; Liangchuan Guo; Junwei Huo; Mingyu Sang; Chunyan Li; Hailian Zang; Yi Cheng (Crop Protection, 2025)

A hybrid governance framework for adaptive and sustainable urban energy management - Renfang Wang; Hong Qiu; Ruyu Liu; Huan Huo; Xu Cheng; Xiufeng Liu (Sustainable Cities and Society, 2025)

Evaluating single-column thermodynamic sea ice models for simulating landfast ice in Prydz Bay, East Antarctica - Yang Liu; Peng Lu; Jiechen Zhao; Miao Yu; Bin Cheng; Lei Wang; Fei Xie; Puzhen Huo; Xuewei Li; Zhijun Li (Ocean Modelling, 2025)

Environmental and health impacts of reduced PM2.5 and trace metals from ship emissions under low-sulfur fuel oil policy in Shanghai, China - Xuyang Dong; Yan Zhang; Guangyuan Yu; Yuqi Xiong; Zimin Han; Juntao Huo; Cheng Huang; Haidong Kan; Mei Zheng; Zhi Ning; Bing Xie (Environmental Pollution, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

GhCTEF2 encodes a PLS-type PPR protein required for chloroplast development and plastid RNA editing in cotton - Huan He; Mengxue Cheng; Bowen Bao; Yanan Tian; Yating Zheng; Yuzhu Huo; Zengqiang Zhao; Zongming Xie; Jianing Yu; Peng He (Plant Science, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Constructing efficient PVDF-HFP-based intercalated composite solid electrolytes via competitive solvation structures for rechargeable lithium metal batteries - Yutong Jing; Shen Liu; Cheng Li; Qiang Lv; Daming Liu; Manxing Huo; Bochen Wu; Siyuan Liu; Yuhang Zhang; Mingyu Yin; Zhipeng He; Dianlong Wang; et al. (Chemical Engineering Journal, 2025)

Efficient elimination of sulfamethoxazole by UV/peroxymonosulfate/sulfite process: Activation of peroxymonosulfate by sulfite via nucleophilic addition - Tongke Wang; Chen Sun; Yang Cheng; Zongli Huo; Jia Gu; Jun Ma (Chemical Engineering Journal, 2025)

Sesquiterpene lactones from Carpesium abrotanoides L. fruits: characterization and bioactivity profiling - Peng-Bo Tang; Xin-Yu Zhang; Chao Zhang; Jiayi Zhang; Shuohong Liu; Francoise Sauriol; Yu-Cheng Gu; Yu-Fang Wang; Chang-Hong Huo (Natural Product Research, 2025)

Photogrammetric system of non-central refractive camera based on two-view 3D reconstruction - Zhen Wu; Mingshu Nan; Haidong Zhang; Junzhou Huo; Shangqi Chen; Guanyu Chen; Zhang Cheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

Distribution characteristics of microplastics in surface waters in the western Pacific Ocean - Cheng Huo; Shoufeng Zhang; Ling Qu; Shuaichen Jin; Cijia Wang; Xiaoting Chu; Maowei Ju (Journal of Oceanology and Limnology, 2025)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Rapid bromate determination using short-column ion chromatography-mass spectrometry: Application to bromate quantification during ozonation - Shi Cheng; Haolin Liu; Yanting Zuo; Feng Zhu; Huaicheng Zhang; Hao Zhang; Shouqiang Huang; Wentao Li; Zongli Huo; Aimin Li (Journal of Environmental Chemical Engineering, 2024)

Neuroprotective Effect of a Multistrain Probiotic Mixture in SOD1G93A Mice by Reducing SOD1 Aggregation and Targeting the Microbiota-Gut-Brain Axis - Zikai Xin; Cheng Xin; Jia Huo; Qi Liu; Hui Dong; Rui Li; Yaling Liu (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the selective loss of motor neurons. A bidirectional communication system known as the “microbiota-gut-brain” axis has a regulatory function in neurodegenerative disorders. The impact of probiotics on ALS through the “microbiota-gut-brain” axis remains uncertain. A longitudinal investigation was conducted to examine the alterations in the structure of the ileum and colon in mutant superoxide dismutase 1 (SOD1 G93A ) transgenic mice models of ALS by using immunofluorescence and Western blotting. Subsequently, the mice were administered a multistrain probiotic mixture (LBE) or vehicle orally, starting from 60 days of age until the terminal stage of the disease. The effects of these agents on the behavior, gut microbiota, microbial metabolites, and pathological processes of the spinal and intestine of SOD1 G93A mice were analyzed, with a focus on exploring potential protective mechanisms. SOD1 G93A mice exhibit various structural abnormalities in the intestine. Oral administration of LBE improved the proinflammatory response, reduced aberrant superoxide dismutase 1 (SOD1) aggregation, and protected neuronal cells in the intestine and spinal cord of SOD1 G93A mice. Furthermore, LBE treatment resulted in a change in intestinal microbiota, an increase in short-chain fatty acid levels, and an enhancement in autophagy flux. SOD1 G93A mice exhibited various structural abnormalities in the intestine. LBE can improve the proinflammatory response, reduce aberrant SOD1 aggregation, and protect neuronal cells in the spinal cord and intestine of SOD1 G93A mice. The positive effect of LBE can be attributed to increased short-chain fatty acids and enhanced autophagy flux.

Strong self-healing close-loop recyclable vitrimers via complementary dynamic covalent/non-covalent bonding - Cheng Wang; Siqi Huo; Guofeng Ye; Qi Zhang; Cheng-Fei Cao; Mark Lynch; Hao Wang; Pingan Song; Zhitian Liu (Chemical Engineering Journal, 2024)

NK cell membrane/MnO2 hybrid nanoparticle-adjuvanted intranasal vaccines synergistically boost protective immunity against H1N1 influenza infection - Hanghang Cheng; Lingli Shen; Xiaoning Liu; Jian Huo; Shuqi Wang; Qun Niu; Haoxiang Yang; Yanan Wu; Xuannian Wang; Gaiping Zhang; Hua He (Chemical Engineering Journal, 2024)

Spontaneous built-in electric field in W-W2C@C heterostructure: Accelerating Sn2- directed migration in Li-S batteries - Henan Jia; Pei Su; Taotao Guo; Mingwei Liu; Tianyu Huo; Shoucong Gao; Ge Jing; Dianbo Ruan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Metal-organic frameworks derived curled sheet-like Cu2O/CuO heterostructure: Low-power N2H4 sensing - Ting Li; Rui Gao; Xianfa Zhang; Xiaoli Cheng; Baosheng Li; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

Enhanced interfacial charge transfer in WO3-Bi2WO6 heterostructures: Toward trace detection of mustard gas simulant - Qiuyue Zheng; Tingting Wang; Xue Ma; Ruibai Ma; Chaobo Huang; Xianfa Zhang; Xiaoli Cheng; Lihua Huo; Zoltán Major; Yingming Xu (Chemical Engineering Journal, 2024)

Considerable enhancement of nanothermites propagation through worm-like expansion of expandable graphite - Xuehang Jiao; Jianyong Xu; Hongbiao Huo; Xiaoting Lei; He Cheng; Chunpei Yu; Wenchao Zhang (Chemical Engineering Journal, 2024)

Construction of highly efficient In2O3/SnO2 sensor for real-time NO2 monitoring at near room temperature - Ji Li; Ming Yang; Jiangbin Guo; Xianfa Zhang; Yingming Xu; Xiaoli Cheng; Lihua Huo (Chemical Engineering Journal, 2024)

Diversity and ecological assembly process of aerobic anoxygenic phototrophic bacteria in a low irradiation area, Three Gorges Reservoir - Lixin Huo; Anran Ma; Hong Liu; Xingzu Wang; Cheng Song (Journal of Environmental Sciences, 2024)

Na+ orientates Jahn-Teller effect to tune Li+ diffusion pathway and kinetics for Single-Crystal Ni-rich LiNixCoyMn1-x-yO2 cathode materials - Jiyuan Jian; Xing Xu; Xiaoyi Pan; Guokang Han; Rang Xiao; Ziwei Liu; Dandan Sun; Xin Zhang; Qingjie Zhou; He Zhu; Geping Yin; Hua Huo; et al. (Chemical Engineering Journal, 2024)

Mild Alkaline-Enhanced depolymerization of Long-Flame coal for the synthesis of Coal-Derived fluorescent carbon dots with application as probes - Junkai Chong; Guangchao Hu; Longheng Xiao; Min Guo; Xiangtao Huo; Jianming Gao; Fangqin Cheng; Mei Zhang (Fuel, 2024)

Elevated plasma solMER concentrations link ambient PM2.5 and PAHs to myocardial injury and reduced left ventricular systolic function in children - Zihan Chen; Xia Huo; Yu Huang; Zhiheng Cheng; Xijin Xu; Zhi Li (Environmental Pollution, 2024)

In-situ controllable preparation of ZIF-8-wrapped ZnO heterojunction nanorods array for ppb-level Cl2 detection operated at near room temperature - Xiaoqian Meng; Rui Gao; Ming Zheng; Xin Zhou; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

Hydroxysafflor Yellow A and Tenuigenin Exhibit Neuroprotection Effects Against Focal Cerebral Ischemia Via Differential Regulation of JAK2/STAT3 and SOCS3 Signaling Interaction - Lu Yu; Cheng Zhang; Lingling Gu; Hong Chen; Yan Huo; Shuyan Wang; Jie Tao; Chuan Xu; Qiujuan Zhang; Mingliang Ma; Jun Zhang (Molecular Neurobiology, 2024)

Ceftiofur in swine manure contributes to reducing pathogens and antibiotic resistance genes during composting - Wenjin Ma; Boyu An; Xiangyue Xu; Meixia Huo; Kun Mi; Xiaoyuan Tian; Ziyan Kou; Aoran Tang; Guyue Cheng; Lingli Huang (Environmental Research, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Coupled of carbon and nitrogen mineralization in rhizosphere soils along a temperate forest altitudinal gradient - Changfu Huo; Jiayu Lu; Liming Yin; Peng Wang; Weixin Cheng (Plant and Soil, 2024)

Microscopic and macroscopic characteristics for coal spontaneous combustion under pre-oxidation and stress - Yong-liang Xu; Xing-wang Huo; Lan-yun Wang; Yi-bo Gao; Ze-cheng Lv; Xin-wei Mi; Yong-sheng Guo (Fuel, 2024)

The insightful water quality analysis and predictive model establishment via machine learning in dual-source drinking water distribution system - Huiping Li; Baiqin Zhou; Xiaoyan Xu; Ranran Huo; Ting Zhou; Xiaochen Dong; Cheng Ye; Tian Li; Li Xie; Weihai Pang (Environmental Research, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

How urban greening policy affects urban ecological resilience: Quasi-natural experimental evidence from three megacity clusters in China - Chang Xu; Xinxin Huo; Yaoxiaoxue Hong; Chang Yu; Martin de Jong; Baodong Cheng (Journal of Cleaner Production, 2024)

CuS assisted Fe(III)-induced peracetic acid activation for bisphenol A degradation: significance of synergetic roles of copper and sulfur in enhanced Fenton-like process - Yongfei Tong; Ningruo Wang; Feng Cheng; Xiaowei Huo; Yang Liu; Yongli Zhang; Xin Cheng; Peng Zhou (Chemical Engineering Journal, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Catalytic activation of persulfate by nanoscale zero-valent iron-derived supported boron-doped porous carbon for bisphenol A degradation - Fuxiang Du; Xiaowei Huo; Chao Xue; Chenggui Zhang; Huichao Wang; Chao Dai; Yang Yang; Cheng Lai; Junjun He (Environmental Science and Pollution Research, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Soil geochemistry prevails over root functional traits in controlling soil organic carbon fractions of the alpine meadow on the Qinghai-Tibet Plateau, China - Yingping Pan; Liang Ren; Jiaxuan Huo; Xiang Xiang; Dehui Meng; Yuanyuan Wang; Cheng Yu; Yiyao Liu; Jingyao Suo; Yongmei Huang (CATENA, 2024)

Co-selection mechanism for bacterial resistance to major chemical pollutants in the environment - Meixia Huo; Xiangyue Xu; Kun Mi; Wenjin Ma; Qin Zhou; Xudong Lin; Guyue Cheng; Lingli Huang (Science of The Total Environment, 2024)

Rapid wet-dry climatic oscillations and large-scale social unrest in ancient China - Xianqiang Meng; Can Zhang; Gen K. Li; Jianru Cheng; Jie Cai; Yilan Liu; Li Huo; Zhenyu Ni; Enlou Zhang (Science Bulletin, 2024)

Nitrogen removal performance and thermodynamic mechanisms of Feammox mediated by ferric pyrophosphate at various pHs - Jiaqi Wang; Cheng Song; Lixin Huo; Xingzu Wang; Hong Liu; Xiaomei Zhang (Journal of Water Process Engineering, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Contrasting effects of temperature and biological processes on aragonite saturation state at the A4HDYD station in the North Yellow Sea - Xuemei Xu; Huade Zhao; Kunpeng Zang; Nan Zheng; Cheng Huo; Xue Deng; Juying Wang (Marine Environmental Research, 2023)

Correction: Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Experimental study on slope morphological characteristics and stability analysis of GCHP engineering in the loess plateau - Zhixin Zhao; Aidi Huo; Yuxiang Cheng; Pingping Luo; Jianbing Peng; Ahmed Elbeltagi; Mohamed EL-Sayed Abuarab; Ali Mokhtar (Advances in Space Research, 2023)

Phosphorus removal by porous aggregate from aerated concrete waste residues：Simulating porous structure, performance optimisation, adsorption mechanisms - Chenchen Gong; Liuqing Huo; Zihui Wang; Chen Sun; Yanfei Wang; Xin Cheng (Journal of Environmental Chemical Engineering, 2023)

NaNO2 additive-assisted Li2O2 decomposition for highly efficient cathode prelithiation of lithium-ion batteries - Rang Xiao; Cong Kang; Yang Ren; Renlong Li; Jiyuan Jian; Binghan Cui; Geping Yin; Xinqun Cheng; Yulin Ma; Hua Huo; Pengjian Zuo; Guokang Han; et al. (Chemical Engineering Journal, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Inactivation of SSIIIa enhances the RS content through altering starch structure and accumulating C18:2 in japonica rice - Yufeng Zhou; Zhenfeng Cheng; Shuo Jiang; Jinxi Cen; Siyuan Yuan; Chao Yu; Shaojie Huo; Ning Zhang; Dianxing Wu; Xiaoli Shu (Carbohydrate Polymers, 2023)

Vibration-enhanced disposable electroanalytical platform for selective analysis of tryptophan in fruits based on molecular imprinting - Ye Cheng; Dong-Yang Tian; Ya-hong Wang; Wu Liu; Xiao-Lei Huo; Ning Bao; Zeng-Qiang Wu (Analytica Chimica Acta, 2023)

High yielded Co–C derived from polyester-Cobalt carbothermal reduction for efficient activation of peroxymonosulfate to degrade levofloxacin - Hang Lv; Yuandong Huo; Manlu Cheng; Zenghui Diao; Gang Song; Diyun Chen; Lingjun Kong (Chemosphere, 2023)

Genetic deletion or pharmacological inhibition of soluble epoxide hydrolase attenuated particulate matter 2.5 exposure mediated lung injury - Juan Zhang; Wen-Hao Zhang; Christophe Morisseau; Min Zhang; Hong-Jun Dong; Qi-Meng Zhu; Xiao-Kui Huo; Cheng-Peng Sun; Bruce D. Hammock; Xiao-Chi Ma (Journal of Hazardous Materials, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Single-ion conductors functionalized graphene oxide enabling solid polymer electrolytes with uniform Li-ion transport toward stable and dendrite-free lithium metal batteries - Zhenyuan Hu; Wei Bao; Yunfeng Zhang; Xin Jiang; Junjie Chen; Yi Zhang; Shikang Huo; Jinnan Zhang; Jinpeng Qin; Shenghan Li; Wenfan Guo; Hansong Cheng (Chemical Engineering Journal, 2023)

Modulating electronic structure of interfacial Fe sites in Fe2N/CoFe2O4 nano-heterostructure for enhancing corrosion-resistance and oxygen electrocatalysis in zinc-air battery - Xiaoqin Xu; Mingyang Liu; Yao Nie; Cheng Wang; Wei Wang; Chuntao Liu; Xinyu Wang; Zhuang Cai; Xiaofeng Liu; Sichen Huo; Bin Liu; Jinlong Zou (Chemical Engineering Journal, 2023)

Seasonal distribution of microplastics in the surface waters of the Yellow Sea, China - Weiwei Zhang; Shoufeng Zhang; Ling Qu; Maowei Ju; Cheng Huo; Juying Wang (Marine Pollution Bulletin, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Microglial Depletion does not Affect the Laterality of Mechanical Allodynia in Mice - Quan Ma; Dongmei Su; Jiantao Huo; Guangjuan Yin; Dong Dong; Kaifang Duan; Hong Cheng; Huiling Xu; Jiao Ma; Dong Liu; Bin Mou; Jiyun Peng; et al. (Neuroscience Bulletin, 2023)

Targeting Peripheral μ-opioid Receptors or μ-opioid Receptor-Expressing Neurons Does not Prevent Morphine-induced Mechanical Allodynia and Anti-allodynic Tolerance - Feng Du; Guangjuan Yin; Lei Han; Xi Liu; Dong Dong; Kaifang Duan; Jiantao Huo; Yanyan Sun; Longzhen Cheng (Neuroscience Bulletin, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

First report of leaf spot on Camellia sinensis caused by Neofusicoccum parvum in China - Xiaoyang Zhang; Xinen Yuan; Shuyuan Cheng; Da Huo; Haozhi Long; Bing Liu; Guihong Xiong; Junxi Jiang (Journal of Plant Pathology, 2023)

Siloxane-type single-ion conductors enable composite solid polymer electrolyte membranes with fast Li+ transporting networks for dendrite-proof lithium-metal batteries - Zhenyuan Hu; Feng Ji; Yunfeng Zhang; Wenfan Guo; Xiao Jing; Wei Bao; Jinpeng Qin; Shikang Huo; Shenghan Li; Yi Zhang; Weizhen Fan; Hansong Cheng (Chemical Engineering Journal, 2023)

Editorial: Exploration and utilization of marine and freshwater high-value biological resources - Feifei Zhu; Liandong Zhu; Wei Liu; Pengfei Cheng; Shuhao Huo (Frontiers in Marine Science, 2023)

A Targeted Lipidomic Reveals CYP450-Derived Oxylipin Linked to the Inflammatory Response by Polycyclic Aromatic Hydrocarbon Exposure in Children - Yifeng Dai; Zhiheng Cheng; Zhijun Zeng; Machteld N. Hylkema; Marijke M. Faas; Xia Huo (Exposure and Health, 2023)

The Paleoenvironment and Mechanisms of Organic Matter Enrichment of Shale in the Permian Taiyuan and Shanxi Formations in the Southern North China Basin - Yanan Wang; Xiulei Cheng; Kai Fan; Zhipeng Huo; Lin Wei (Journal of Marine Science and Engineering, 2023)
The organic-rich shale of the Permian Taiyuan Formation (TYF) and Shanxi Formation (SXF) in the Southern North China Basin (SNCB) is considered a potential shale gas source. The shale was formed in a marine-continental transitional sedimentary environment, which has rarely been studied, with the enrichment mechanisms of organic matter (OM) remaining unclear. This study investigated the controlling factors and enrichment mechanisms of OM by analyzing the total organic carbon (TOC) content, paleoclimate, paleoproductivity, sedimentation rate, redox, and paleosalinity. The TOC of the TYF ranged from 0.92 to 7.43 wt.%, with an average of 2.48 wt.%, which was higher than that of the SXF (TOC = 0.36–5.1 wt.%, average of 1.68 wt.%). These geochemical indices suggest that both the TYF and SXF were deposited in warm and humid paleoclimates, with relatively high biological productivity and sedimentation rates. During the deposition process, the TYF experienced frequent transgression and regression events, leading to an enhancement of water reducibility, a relatively high sedimentation rate, reduced OM oxidation, and rapid deposition of OM, which were conducive to the preservation of OM. Moreover, a high biological productivity increased respiratory oxygen consumption in the water column, which could lead to OM accumulation. However, the regression event experienced by the SXF reduced the paleoproductivity and sedimentation rate and increased water oxidation, leading to a decrease in OM. The main controlling factors for the enrichment of OM in the TYF and SXF were the sedimentation rate, paleoproductivity, and redox conditions, thus establishing the enrichment models for OM in the TYF and SXF. This study is conducive to understanding shale enrichment mechanisms and guiding shale gas exploration.

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Measuring green development index and coupling coordination of mining industry: An empirical analysis based on panel data in China - Dejiang Luo; Jie Huang; Hao Wu; Long Cheng; Zhilei Huo (Journal of Cleaner Production, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

GSH and H2O2 dynamic correlation in the ferroptosis pathways revealed by engineered probe in tumor and kidney injury - Yuting Wang; Huming Yan; Yongkang Yue; Yongbin Zhang; Fangjun Huo; Fangqin Cheng; Caixia Yin (Chemical Engineering Journal, 2023)

Importance of amylose chain-length distribution in determining starch gelatinization and retrogradation property of wheat flour in the presence of different salts - Enpeng Li; Jiaqi Lv; Dongao Huo; Bin Jia; Cheng Li (Carbohydrate Polymers, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Vibration for enhancement of electrochemical analysis of biomolecules in a droplet on the rough surface of a disposable working electrode - Ya-Hong Wang; Xiang-Yun Lin; Ye Cheng; Hua Wang; Wu Liu; Xiang-Kai Zhuge; Xiao-Lei Huo; Ning Bao (Analytica Chimica Acta, 2023)

Spatial confinement-based Figure-of-Eight nanoknots accelerated simultaneous detection and imaging of intracellular microRNAs - Huo Xu; Yanhui Zheng; Xiaojun Fang; Yinghao Cheng; Jianguo Xu; Jie Wang; Hongxia Li; Lee Jia; Chang Xue (Analytica Chimica Acta, 2023)

Galactosyltransferase GhRFS6 interacting with GhOPR9 involved in defense against Verticillium wilt in cotton - Baiyang Chang; Lihong Zhao; Zili Feng; Feng Wei; Yalin Zhang; Yihao Zhang; Peng Huo; Yong Cheng; Jinglong Zhou; Hongjie Feng (Plant Science, 2023)

Gold − Titanium dioxide heterojunction for enhanced sonodynamic mediated biofilm eradication and peri-implant infection treatment - Fang Li; Qiyuan Pan; Yun Ling; Jingying Guo; Yaru Huo; Chao Xu; Manwen Xiong; Meng Yuan; Ziyong Cheng; Min Liu; Jun Lin (Chemical Engineering Journal, 2023)

Novel in-situ deposited V2O5 nanorods array film sensor with enhanced gas sensing performance to n-butylamine - Xuemei Sun; Rui Gao; Yuanyuan Wu; Xianfa Zhang; Xiaoli Cheng; Shan Gao; Yingming Xu; Lihua Huo (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Developing a UV dosing strategy for UV/chlorine process towards the trade-off between pharmaceuticals and personal care products degradation and disinfection by-products formation - Shi Cheng; Yanting Zuo; Aimin Li; Haohan Jiang; Wenliang Ji; Ji Wu; Wentao Li; Zhe Wang; Yonglin Zhou; Feng Zhu; Wei He; Zongli Huo; et al. (Journal of Cleaner Production, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

A P/Si-containing polyethylenimine curing agent towards transparent, durable fire-safe, mechanically-robust and tough epoxy resins - Cheng Wang; Siqi Huo; Guofeng Ye; Pingan Song; Hao Wang; Zhitian Liu (Chemical Engineering Journal, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Minocycline Ameliorates Chronic Unpredictable Mild Stress-Induced Neuroinflammation and Abnormal mPFC-HIPP Oscillations in Mice - Sidra Tabassum; Afzal Misrani; Qingwei Huo; Adeel Ahmed; Cheng Long; Li Yang (Molecular Neurobiology, 2022)

Trimethylamine N-oxide facilitates the progression of atrial fibrillation in rats with type 2 diabetes by aggravating cardiac inflammation and connexin remodeling - Wan-Ying Jiang; Jun-Yu Huo; Sheng-Chan Wang; Yan-Di Cheng; Yi-Ting Lyu; Zhi-Xin Jiang; Qi-Jun Shan (Journal of Physiology and Biochemistry, 2022)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

O-GlcNAc Transferase (OGT) Protects Cerebral Neurons from Death During Ischemia/Reperfusion (I/R) Injury by Modulating Drp1 in Mice - Jingru Zhao; Lipeng Dong; Tiantian Huo; Jinming Cheng; Xiaojuan Li; Xiaojuan Huangfu; Sujuan Sun; Hebo Wang; Litao Li (NeuroMolecular Medicine, 2022)

Temporal dynamics of fine root production, mortality and turnover deviate across branch orders in a larch stand - Changfu Huo; Jiacun Gu; Lizhong Yu; Peng Wang; Weixin Cheng (Oecologia, 2022)

3D carbon aerogel from waste corrugated cardboard as a photothermal reservoir for solar steam generation - Hanxin Huo; Yuhui Ma; Yu Cheng; Junrui Cao (Environmental Science and Pollution Research, 2022)

Effects and mechanisms of constructed wetlands with different substrates on N2O emission in wastewater treatment - Junyu Huo; Xiaojin Hu; Shiyi Cheng; Huijun Xie; Zhen Hu; Haiming Wu; Shuang Liang (Environmental Science and Pollution Research, 2022)

Characterization and genomic analysis of a Demerecviridae phage SP76 with lytic multiple-serotypes of Salmonella - Hui Wang; Yun Shen; Pei LI; Yuyi Xiao; Yanxiu Li; Xiapei Hu; Zhuohao Wang; Zile Cheng; Zitong Wang; Qingxin Liu; Si Qin; Xiang Huo; et al. (Archives of Microbiology, 2022)

Transformation of bisphenol AF by chlorination: kinetic study and product identification - Jingyi Chang; Wenrui Xiang; Ruijuan Qu; Cheng Sun; Zunyao Wang; Feng Zhu; Zongli Huo (Environmental Science and Pollution Research, 2021)

E-waste polycyclic aromatic hydrocarbon (PAH) exposure leads to child gut-mucosal inflammation and adaptive immune response - Guangcan Chen; Xia Huo; Xiuli Luo; Zhiheng Cheng; Yuling Zhang; Xijin Xu (Environmental Science and Pollution Research, 2021)

Hemoglobin Extracted From Perinereis aibuhitensis Acts as a Cell Culture Medium Supplement to Reduce Apoptosis - Qianyu Huo; Jing Liu; You Cheng; Bin Cao; Ming Lei; Yunde Liu (Frontiers in Marine Science, 2021)
The environmental oxygen concentration is a crucial factor affecting cell proliferation. Owing to the reversible binding property of hemoglobin to oxygen, it can be utilized to regulate the oxygen concentration in vitro , and its ability to reduce apoptosis can be evaluated. In this study, a process comprising isolation, purification, and extraction was used to obtain hemoglobin from Perinereis aibuhitensis , a polychaete invertebrate. Extracts were separated and characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Extract component identity was confirmed by matrix-assisted laser desorption time-of-flight mass spectrometry analysis, with the molecular weight determined as 412,216.6875 Da. The oxygen carrying capacity of P. aibuhitensis hemoglobin was comparable with that of human hemoglobin. P. aibuhitensis hemoglobin remarkably downregulated the apoptosis rate. Reactive oxygen species (ROS) assays confirmed the reduction in ROS production, enabling a better elucidation of the mechanism underlying the decrease in apoptosis. These results suggested that P. aibuhitensis hemoglobin is a natural oxygen carrier, that, owing to its low-cost and accessibility, can be considered a candidate for culture medium supplement to reduce the apoptosis rate.

Oxidation of benzophenone-3 in aqueous solution by potassium permanganate: kinetics, degradation products, reaction pathways, and toxicity assessment - Wanming Cao; Nannan Wu; Ruijuan Qu; Cheng Sun; Zongli Huo; Jamaan S. Ajarem; Ahmed A. Allam; Zunyao Wang; Feng Zhu (Environmental Science and Pollution Research, 2021)

Multiple diversity facets of crucial microbial groups in biological soil crusts promote soil multifunctionality - Hua Li; Youxin Chen; Gongliang Yu; Federico Rossi; Da Huo; Roberto De Philippis; Xiaoli Cheng; Weibo Wang; Renhui Li (Global Ecology and Biogeography, 2021)
Aim Microbial diversity is one of the most important factors for maintaining the performance of multiple functions in soils (multifunctionality). However, existing studies typically consider the taxonomic richness or Shannon diversity of the entire community. We know little about the connection network of taxonomic and phylogenetic facets of diversity and their collective impact on multifunctionality. In this study, the linkages of effects of diversity within functional groups were disentangled in drylands. Location The central Tibetan Plateau. Time period Present. Major taxa studied Phototrophs and diazotrophs (mainly cyanobacteria). Methods Given the carbon‐ and nitrogen‐limited nature of drylands, we conducted a high‐throughput sequencing of C/N‐fixing functional groups from biocrusts and evaluated multiple facets of diversity (i.e., richness, evenness and phylogeny‐related trait dissimilarity), together with seven crucial variables of soil functioning to calculate multifunctionality. The relationships between multifaceted diversity and abundance with individual functions and multifunctionality were validated by a set of solid statistical analyses. Results We found that the integrated biodiversity index was a stronger predictor of multifunctionality than richness. The divergent performance of different facets of diversity determined the idiosyncratic effect of each functional group on soil multifunctionality. Moreover, the evaluation of functional significance at the species level gave important clues on the trade‐offs and redundancy in each functional group, explaining the distinct patterns of effects of diversity. Richness was the dominant factor for diazotrophs to maximize multifunctionality, whereas phylogenetic dissimilarity was the essential one for phototrophs. Main conclusions Our study demonstrated that multiple facets of diversity should be considered when assessing the effects of biodiversity. In contrast to the community level, within‐functional group measures might adequately capture the features of diversity that are most correlated with soil multifunctionality. Our results provide a perspective to bridge the gap between taxonomic and trait‐based approaches for elucidating the biodiversity–ecosystem function relationship.

Correction to: High‑depth resequencing of 312 accessions reveals the local adaptation of foxtail millet - Congcong Li; Genping Wang; Haiquan Li; Guoliang Wang; Jian Ma; Xin Zhao; Linhe Huo; Liquan Zhang; Yanmiao Jiang; Jiewei Zhang; Guiming Liu; Guoqing Liu; et al. (Theoretical and Applied Genetics, 2021)

High-depth resequencing of 312 accessions reveals the local adaptation of foxtail millet - Congcong Li; Genping Wang; Haiquan Li; Guoliang Wang; Jian Ma; Xin Zhao; Linhe Huo; Liquan Zhang; Yanmiao Jiang; Jiewei Zhang; Guiming Liu; Guoqing Liu; et al. (Theoretical and Applied Genetics, 2021)

Identification and functional characterization of a PDR transporter in Tripterygium wilfordii Hook.f. that mediates the efflux of triptolide - Guopeng Miao; Juan Han; Yan-bo Huo; Cheng-run Wang; Shun-chang Wang (Plant Molecular Biology, 2021)

Analysis of loess fracture on slope stability based on centrifugal model tests - Yuxiang Cheng; Aidi Huo; Zhixin Zhao; Jianbing Peng (Bulletin of Engineering Geology and the Environment, 2021)

Improvement and application of preprocessing technique for multitrace seismic impedance inversion - Zhong Fei-Yan; Zhou Lu; Dai Rong-Huo; Yin Cheng; Zhao Hu; Xu Liang-Jun (Applied Geophysics, 2021)

Size distribution of PM20 observed to the north of the Tibetan Plateau - Cheng-long Zhou; Fan Yang; Wen Huo; Ali Mamtimin; Xing-hua Yang (Journal of Mountain Science, 2021)

UAV-based gully retrogressive erosion status dynamic variability investigations in Chinese Loess Plateau - Huo Aidi; Chen Siming; Peng Jianbing; Cheng Yuxiang (Arabian Journal of Geosciences, 2021)

Protective Effects of Bacillus subtilis ANSB060, Bacillus subtilis ANSB01G, and Devosia sp. ANSB714-Based Mycotoxin Biodegradation Agent on Mice Fed with Naturally moldy Diets - Yongpeng Guo; Xueting Huo; Lihua Zhao; Qiugang Ma; Jianyun Zhang; Cheng Ji; Lihong Zhao (Probiotics and Antimicrobial Proteins, 2020)

RIG-I aggravates interstitial fibrosis via c-Myc-mediated fibroblast activation in UUO mice - Zhuanli Zhou; Jiayun Ni; Jingyao Li; Chuanbing Huo; Naijun Miao; Fan Yin; Qian Cheng; Dan Xu; Hongyan Xie; Panpan Chen; Peiqing Zheng; Yingying Zhang; et al. (Journal of Molecular Medicine, 2020)
Progressive tubulointerstitial fibrosis is the common final outcome for all kidney diseases evolving into chronic kidney disease (CKD), whereas molecular mechanisms driving fibrogenesis remain elusive. Retinoic acid-inducible gene-I (RIG-I), an intracellular pattern recognition receptor, is originally identified participating in immune response by recognizing virus RNA. Here, we revealed for the first time that RIG-I was induced in unilateral ureteral obstruction (UUO) and folic acid (FA) renal fibrosis models and moderate-degree renal fibrosis patients. Besides, we found RIG-I was mainly located in renal tubular epithelial cells and promoted the production and release of inflammatory cytokines, such as interleukin (IL)-1β and IL-6 through activation of NF-κB. Inflammatory cytokines released by tubular epithelial cells activated c-Myc-mediated TGF-β/Smad signaling in fibroblasts, which in turn aggravated interstitial fibrosis by promoting fibroblast activation and production of extracellular matrix components (ECM). Deficiency of RIG-I attenuated renal fibrosis by the regulation of inflammatory responses, c-Myc expression, and fibroblast activation. Besides, gene silencing of RIG-I reduced inflammatory cytokines in cultured tubular epithelial cells treated with Angiotensin II. Knockdown of c-Myc or c-Myc inhibitor blocked IL-1β-induced fibroblast activation. Collectively, our study demonstrates that RIG-I plays a significant role in the progress of renal fibrosis via regulating c-Myc-mediated fibroblast activation. Key messages • RIG-I was constantly elevated in kidneys from renal fibrotic mice. • RIG-I facilitated inflammatory cytokine production in tubular epithelial cells. • RIG-I aggravated renal fibrosis via c-Myc-mediated TGF-β/Smad activation.

Multifunctionality of biocrusts is positively predicted by network topologies consistent with interspecies facilitation - Hua Li; Da Huo; Weibo Wang; Youxin Chen; Xiaoli Cheng; Gongliang Yu; Renhui Li (Molecular Ecology, 2020)
The potential of biodiversity loss to impair the delivery of ecosystem services has motived ecologists to better understand the relationship between biodiversity and ecosystem functioning. Although increasing evidence underlines the collective contribution of different biodiversity components on the simultaneous performance of multiple functions (multifunctionality), we know little about the trade‐offs between individual diversity effects and the extent to which they determine multifunctionality differentially. Here, at a subcontinental scale of 62 dryland sites, we show in phototrophic microbiota of biological soil crusts (biocrusts) that, whereas richness alone is unable to guarantee the maxima of multifunctional performance, interspecies facilitation and compositional identity are particularly stronger but often neglected predictors. The inconsistent effects of different biodiversity components imply that soil multifunctionality can be lost despite certain species remaining present. Moreover, we reveal a significant empirical association between species functional importance and its topological feature in co‐occurrence networks, indicating a functional signal of species interaction. Nevertheless, abundant species tend to isolate and merely interact within small topological structures, but rare species were tightly connected in complicated network modules. Our findings suggest that abundant and rare species of soil phototrophs exhibit distinct functional relevance. These results give a comprehensive view of how soil constructive species drive multifunctionality in biocrusts and ultimately promote a deeper understanding of the consequences of biodiversity loss in real‐world ecosystems.

Fine Mapping of the High-pH Tolerance and Growth Trait-Related Quantitative Trait Loci (QTLs) and Identification of the Candidate Genes in Pacific White Shrimp (Litopenaeus vannamei) - Wen Huang; Chuhang Cheng; Jinshang Liu; Xin Zhang; Chunhua Ren; Xiao Jiang; Ting Chen; Kaimin Cheng; Huo Li; Chaoqun Hu (Marine Biotechnology, 2020)

Rapid evolution of α-gliadin gene family revealed by analyzing Gli-2 locus regions of wild emmer wheat - Naxin Huo; Tingting Zhu; Shengli Zhang; Toni Mohr; Ming-Cheng Luo; Jong-Yeol Lee; Assaf Distelfeld; Susan Altenbach; Yong Q. Gu (Functional & Integrative Genomics, 2019)

Bioaccumulation and health risk assessment of trace metals in fish from freshwater polyculture ponds in Chengdu, China - Xiaoxun Xu; Qinglin Huo; Yuanyuan Dong; Shirong Zhang; Zhanbiao Yang; Junren Xian; Yuanxiang Yang; Zhang Cheng (Environmental Science and Pollution Research, 2019)

An indole diterpenoid isolated from the fungus Drechmeria sp. and its antimicrobial activity - Jia-Hao Liang; Xiao-Kui Huo; Zhong-Bin Cheng; Cheng-Peng Sun; Jian-Chao Zhao; Xiao-Hui Kang; Tian-Yuan Zhang; Zhong-Jian Chen; Tian-Mei Yang; Ying-Ying Wu; Xiao-Peng Deng; Yi-Xuan Zhang (Natural Product Research, 2019)

Performance of yeast-like cell counting (YLCC) using the Sysmex UF-1000i for clinical candiduria screening - He Zhengxin; Zhang Haipu; Cheng Yan; Ran Xiangyang; Chen Jing; Huo Xiaosai; Wang Fukun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Meteorological conditions during a severe, prolonged regional heavy air pollution episode in eastern China from December 2016 to January 2017 - Xueliang Deng; Weihua Cao; Yanfeng Huo; Guanying Yang; Caixia Yu; Dongyan He; Weitao Deng; Wei Fu; Heming Ding; Jing Zhai; Long Cheng; Xuhui Zhao (Theoretical and Applied Climatology, 2019)

Multiple hydrological models comparison and an improved Bayesian model averaging approach for ensemble prediction over semi-humid regions - Wenbo Huo; Zhijia Li; Jingfeng Wang; Cheng Yao; Ke Zhang; Yingchun Huang (Stochastic Environmental Research and Risk Assessment, 2019)

Chemical constituents from Alisma plantago - aquatica subsp . orientale (Sam.) Sam and their anti-inflammatory and antioxidant activities - Xin-Yu Zhao; Gang Wang; Yan Wang; Xiang-Ge Tian; Jian-Chao Zhao; Xiao-Kui Huo; Cheng-Peng Sun; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Xun Wang (Natural Product Research, 2018)

Chimeric GII.3/GII.6 norovirus capsid (VP1) proteins: characterization by electron microscopy, trypsin sensitivity and binding to histo-blood group antigens - Shuhuan Ma; Lijun Zheng; Jinjin Liu; Wenhui Wang; Jie Ma; Xuhui Cheng; Lili Ge; Mingchen Wang; Yuqi Huo; Shuo Shen (Archives of Virology, 2018)

One new indolocarbazole alkaloid from the Streptomyces sp. A22 - Xiangwei Cheng; Biao Zhou; Huazhang Liu; Chao Huo; Wanjing Ding (Natural Product Research, 2018)

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

Two new protostane-type triterpenoids from Alisma orientalis - Xiu-Lan Xin; Xin-Yu Zhao; Xiao-Kui Huo; Xiang-Ge Tian; Cheng-Peng Sun; Hou-Li Zhang; Yan Tian; Yong Liu; Xun Wang (Natural Product Research, 2018)

Attribution assessment and projection of natural runoff change in the Yellow River Basin of China - Zhe Yuan; Denghua Yan; Zhiyong Yang; Jijun Xu; Junjun Huo; Yanlai Zhou; Cheng Zhang (Mitigation and Adaptation Strategies for Global Change, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Erratum to: Polymorphism of rs3737597 in DISC1 Gene on Chromosome 1q42.2 in sALS Patients: a Chinese Han Population Case–Control Study - Libin Deng; Liwei Huo; Jie Zhang; Xiaoli Tang; Zhujun Cheng; Gang Li; Xin Fang; Jinsong Xu; Xiong Zhang; Renshi Xu (Molecular Neurobiology, 2017)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Comparative Analysis of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) of Streptococcus thermophilus St-I and its Bacteriophage-Insensitive Mutants (BIM) Derivatives - Wan Li; Xin Bian; Smith Etareri Evivie; Gui-cheng Huo (Current Microbiology, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Ecological functions of uncultured microorganisms in the cobalt-rich ferromanganese crust of a seamount in the central Pacific are elucidated by fosmid sequencing - Yingyi Huo; Hong Cheng; Anton F. Post; Chunsheng Wang; Xiawei Jiang; Jie Pan; Min Wu; Xuewei Xu (Acta Oceanologica Sinica, 2015)

Proteomic analysis of the response to NaCl stress of Lactobacillus bulgaricus - Chun Li; Pei-Zhao Li; Jin-Wei Sun; Gui-Cheng Huo; Li-Bo Liu (Biotechnology Letters, 2014)

Associations between tumor necrosis factor alpha gene polymorphism and sarcoidosis: a meta-analysis - Hao Jun Xie; Muli Wu; Yi Niu; Bin Shen; Yating Huo; Yuanxiong Cheng (Molecular Biology Reports, 2014)

Association between the IFN-γ and IL-1 genetic polymorphisms and colorectal cancer in the Chinese Han population - BAO-YING FEI; HUO-XIANG LV; YONG-WEI CHENG; JIANG-MING YANG (Journal of Genetics, 2014)

Streptomyces jiujiangensis sp. nov., isolated from soil in South China - Bing-Huo Zhang; Juan Cheng; Li Li; Yong-Guang Zhang; Hong-Fei Wang; Han-Quan Li; Jian-Yuan Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Microlunatus cavernae sp. nov., a novel actinobacterium isolated from Alu ancient cave, Yunnan, south-west China - Juan Cheng; Wei Chen; Bing Huo-Zhang; Salam Nimaichand; En-Min Zhou; Xin-Hua Lu; Hans-Peter Klenk; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Isolation and identification of a wheat gene encoding a zinc finger protein (TaZnFP) responsive to abiotic stresses - Dong-Hong Min; Yue Zhao; Dong-Ying Huo; Lian-Cheng Li; Ming Chen; Zhao-Shi Xu; You-Zhi Ma (Acta Physiologiae Plantarum, 2013)

Exploring the diploid wheat ancestral A genome through sequence comparison at the high-molecular-weight glutenin locus region - Lingli Dong; Naxin Huo; Yi Wang; Karin Deal; Ming-Cheng Luo; Daowen Wang; Olin D. Anderson; Yong Qiang Gu (Molecular Genetics and Genomics, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Potential Contribution of Hypoxia-Inducible Factor-1α, Aquaporin-4, and Matrix Metalloproteinase-9 to Blood–Brain Barrier Disruption and Brain Edema After Experimental Subarachnoid Hemorrhage - Zhong Wang; Cheng-Jie Meng; Xu-Ming Shen; Zhang Shu; Chao Ma; Guo-Qing Zhu; Hui-Xiang Liu; Wei-Chun He; Xue-Bo Sun; Lei Huo; Jian Zhang; Gang Chen (Journal of Molecular Neuroscience, 2012)

Cloning, expression and characterization of a halotolerant esterase from a marine bacterium Pelagibacterium halotolerans B2T - Xiawei Jiang; Yingyi Huo; Hong Cheng; Xinqi Zhang; Xufen Zhu; Min Wu (Extremophiles, 2012)

Paleomagnetic results of Late Paleozoic rocks from northern Qiangtang Block in Qinghai-Tibet Plateau, China - Xin Cheng; HanNing Wu; Qiang Guo; BaoNing Hou; LingYan Xia; HaiJun Wang; ZongBao Diao; FeiFei Huo; WenHua Ji; RongShe Li; ShouJian Chen; ZhenMing Zhao; et al. (Science China Earth Sciences, 2012)

Comparison of a high-density genetic linkage map to genome features in the model grass Brachypodium distachyon - Naxin Huo; David F. Garvin; Frank M. You; Stephanie McMahon; Ming-Cheng Luo; Yong Q. Gu; Gerard R. Lazo; John Philip Vogel (Theoretical and Applied Genetics, 2011)

Complete genome sequence analysis of tick-borne encephalitis viruses isolated in northeastern China - Bing-Yin Si; Tao Jiang; Yu Zhang; Yong-Qiang Deng; Qiu-Bo Huo; Yuan-Chun Zheng; E-De Qin; Cheng-Feng Qin; Qing-Yu Zhu (Archives of Virology, 2011)

Localization and Characterization of GTP-Binding Protein CT703 in the Chlamydia trachomatis-Infected Cells - Kun Du; FuYan Wang; Zhi Huo; Jie Wang; Wen Cheng; Ming Li; Ping Yu (Current Microbiology, 2011)

Molecular cloning, characterization and expression analysis of CmAPX - Hong Cheng; Qiwei He; Yumeng Huo; Lixia Hou; Junfen Lv (Molecular Biology Reports, 2009)

Structural characterization of Brachypodium genome and its syntenic relationship with rice and wheat - Naxin Huo; John P. Vogel; Gerard R. Lazo; Frank M. You; Yaqin Ma; Stephanie McMahon; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Plant Molecular Biology, 2009)

Simulating carbon sequestration and GHGs emissions in Abies fabric forest on the Gongga Mountains using a biogeochemical process model Forest-DNDC - Xuyang Lu; Genwei Cheng; Feipeng Xiao; Changfu Huo (Journal of Mountain Science, 2008)

The nuclear genome of Brachypodium distachyon: analysis of BAC end sequences - Naxin Huo; Gerard R. Lazo; John P. Vogel; Frank M. You; Yaqin Ma; Daniel M. Hayden; Devin Coleman-Derr; Theresa A. Hill; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Functional & Integrative Genomics, 2008)

The transport kinetics of lanthanide species in a single erythrocyte probed by confocal laser scanning microscopy - Y. Cheng; Qihua Huo; Jingfen Lu; Rongchang Li; K. Wang (JBIC Journal of Biological Inorganic Chemistry, 1999)